Internalisasi Nilai-Nilai Pendidikan Islam Melalui Media Gender Typed Play - Nitria Anggriani; Muhaini Muhaini; Muhammad Iqbal; Rita Sari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The internalization of Islamic values must be done from the beginning, so that students understand and do not misunderstand gender equality in today's unstoppable flow of information. The purpose of this study is to describe the use of gendered media that are socialized through classroom learning. This type of research is quantitative research. The sample of this research is 28 students. Data collection was carried out using a questionnaire. The results of incorporating Islamic educational values through gender learning media in fourth grade students were successful, building on the problems that arose after researchers tried to introduce them into learning media by linking Islamic values. Students can recognize true Islamic values, especially those that are in accordance with gender roles that are in accordance with Islamic values. Students can recognize the significance of amanah content in learning